2012
DOI: 10.1007/s13300-012-0017-4
|View full text |Cite
|
Sign up to set email alerts
|

Glucose Meters with Built-In Automated Bolus Calculator: Gadget or Real Value for Insulin-Treated Diabetic Patients?

Abstract: Self-monitoring of blood glucose is now widely recognized as efficacious to enhance and facilitate diabetes management. More than just a means of recording and storing data, some blood glucose meters (BGMs) are now designed with an embedded automated bolus calculator (ABC) with the goal to propose patients recommendations about insulin dosage. The growing literature in this field tends to claim that these new smart BGMs make patient’s life easier and decision making safer. The main purpose of this review is to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
28
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 47 publications
0
28
0
Order By: Relevance
“…21,22 The use of bolus calculators for FIT dramatically decreases errors in insulin dose calculation. 23 The use of other pump options such as the temporary basal rate also provides an improvement in HbA1c levels. 24 Seasonal switch to MDI concerned only 10% of our cohort.…”
Section: Discussionmentioning
confidence: 99%
“…21,22 The use of bolus calculators for FIT dramatically decreases errors in insulin dose calculation. 23 The use of other pump options such as the temporary basal rate also provides an improvement in HbA1c levels. 24 Seasonal switch to MDI concerned only 10% of our cohort.…”
Section: Discussionmentioning
confidence: 99%
“…The most recent development in glucose meters technology is embedding an automated bolus calculator with the goal to propose recommendations about insulin dosage to patients, and there is increasing evidence that these new smart devices make patients' decision-making safer. 6 At present, SMBG is widely used and widely reimbursed and is considered an integral part of treatment for people with type 1 diabetes and those with insulin-treated type 2 diabetes. 7,8 In one study, SMBG usage between 1993 and 2009 increased from 67% to 90% in insulin-treated type 2 diabetes patients and from 9% to 27% in type 2 diabetes patients on oral antihyperglycemic agent therapy.…”
Section: Self-monitoring Of Blood Glucose In Diabetesthe Evidencementioning
confidence: 99%
“…5 A recent review on the use of BGMs with builtin bolus calculators concluded that these are effective motivational tools which empower the patient through an increased capability to translate self-monitored blood glucose values into appropriate therapeutic decisions. 6 A small proportion of patients, however, prefer familiar routines, calculating their own or using prescribed insulin doses; this must be acknowledged and supported. Potential risks of hypoglycemia in any automated system must also be borne in mind, and appropriate patient education in this respect is important.…”
Section: Discussionmentioning
confidence: 99%